Inhibitory Effects of Macelignan on Tau Phosphorylation and Aβ Aggregation in the Cell Model of Alzheimer's Disease - Gu, Liang; Cai, Nan; Li, Meiting; Bi, Decheng; Yao, Lijun; Fang, Weishan; Wu, Yan; Hu, Zhangli; Liu, Qiong; Lin, Zhijian; Lu, Jun; Xu, Xu (Frontiers in Nutrition, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disorder mainly affecting old population. In this study, two Tau overexpressing cell lines (SH-SY5Y/Tau and HEK293/Tau), N2a/SweAPP cell line, and 3×Transgene (APPswe/PS1M146V/TauP301L) mouse primary nerve cell lines were used as AD models to study the activity and molecular mechanism of macelignan, a natural compound extracted from Myristica fragrans, against AD. Our study showed that macelignan could reduce the phosphorylation of Tau at Thr 231 site, Ser 396 site, and Ser 404 site in two overexpressing Tau cell lines. It also could decrease the phosphorylation of Tau at Ser 404 site in mouse primary neural cells. Further investigation of its mechanism found that macelignan could reduce the phosphorylation of Tau by increasing the level of autophagy and enhancing PP2A activity in Tau overexpressing cells. Additionally, macelignan could activate the PERK/eIF2α signaling pathway to reduce BACE1 translation, which further inhibits the cleavage of APP and ultimately suppresses Aβ deposition in N2a/SweAPP cells. Taken together, our results indicate that macelignan has the potential to be developed as a treatment for AD.